Wavelength calculation using dimensional analysis technique. - Torres Hugues, Ronnie (Rev. Téc. Fac. Ing. Univ. Zulia)
In this article, a dimensional analysis is made thorough Pi theorem to obtain an explicit expression to calculate wavelength in Transitional Water. From this, 3 variants of pairs of Pi parameters are obtained, so from an experiment with 1369 values the behavior is describe and many expressions from a curve fit for each Pi parameter are obtained. Then, the best expression is selected taking into account the correlation coefficient and Fit Standard Error.